Poster: The future to personalize medicine is in your smart-device - Mohanty S.; Toshniwal M.; Dutta T.; Gupta H.P. (My University, 2025)
Most medicine taker may not aware of the details of a drug's brand name and manufacturer, indications, dosage, interac- tions, and side effects of the medicine. In order to avoid over-prescriptions, to prevent medicinal misuse and side ef- fects of medicine, it is necessary for medicine takers to be provided with the detailed information about the medicine. This can be achieved by personalizing the medicines us- ing smart-devices. In this work, we proposed a personal- ized medicine system to provide the information about a medicine through automatic text recognition from the im- prints of the medicine and transmission using smart-devices. The system is fast enough to display the associated informa- tion of the medicine in real-time. © 2016 Copyright held by the owner/author(s).